Work Life Balance of Female Employees Across Generations in Indonesia - Joeliaty; Marthalina; Firmansyah, Yayan; Muhammad, A Fadel (PT. Maju Malaqbi Makkarana, 2025)
This study explores work-life balance among female government employees across generations, with a focus on gender-related challenges. Women are hypothesised to face imbalances due to dual roles at work and home. Using a phenomenological approach and descriptive quantitative analysis, the study finds that Indonesian women across generations generally experience moderate work-life balance. Notably, Baby Boomers (60–78 years) and Generation Z (12–27 years) report higher balance, while Generation X (44–59 years) and Millennials (28–43 years) face lower balance due to simultaneous career and family responsibilities. The study offers generationally tailored suggestions, although results may not generalise to women in sectors like banking or private industry. Implications include the need for organisations to act as facilitators, supporting female employees to ensure psychological well-being and sustained performance.